PENGARUH DISIPLIN KERJA DAN KEPEMIMPINAN TERHADAP KINERJA KARYAWAN ADMINISTRASI FAKULTAS EKONOMI UNIVERSITAS RIAU - Agus Dian Pramana Putra; Susi Hendriani; Henni Noviasari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The research was conducted at the offices of the Bureau of Economics Faculty, University of Riau, Pekanbaru. The study took place from December 2012. The purpose of this study is to analyze the effect of labor discipline and leadership to employee performance Administration Faculty of Economics, University of Riau. In collecting the data, the population in this study were all employees of Administration Faculty of Economics, University of Riau are working actively in 2012 which amounted to 65 people, in this study the sampling method using sensus. The statistical data analysis using SPSS (statistical program for social) is multiple linear regression. The results showed that labor discipline, and leadership either simultaneously or partial effect on employee performance. The most dominant variable in affecting the performance of the employee is working discipline, and leadership.Keywords : Job Discipline, Leadership, and Performance.